2015
DOI: 10.1016/j.diff.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal cohesion of the structural, functional and molecular characteristics of the developing zebrafish heart

Abstract: Heart formation is a complex, dynamic and highly coordinated process of molecular, morphogenetic and functional factors with each interacting and contributing to formation of the mature organ. Cardiac abnormalities in early life can be lethal in mammals but not in the zebrafish embryo which has been widely used to study the developing heart. While early cardiac development in the zebrafish has been well characterized, functional changes during development and how these relate to architectural, cellular and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
(72 reference statements)
0
9
1
Order By: Relevance
“…Expression appears at 72 hpf and is not seen at earlier time points, including 48 hpf. The zebrafish heart undergoes a morphological and functional change from a simple two-chambered tube-shaped organ at 48 hpf into a multi-layered and mature functioning organ by 120 hpf [Matrone et al, 2015]. …”
Section: Discussionmentioning
confidence: 99%
“…Expression appears at 72 hpf and is not seen at earlier time points, including 48 hpf. The zebrafish heart undergoes a morphological and functional change from a simple two-chambered tube-shaped organ at 48 hpf into a multi-layered and mature functioning organ by 120 hpf [Matrone et al, 2015]. …”
Section: Discussionmentioning
confidence: 99%
“…Many other events occurring at postembryonic stages in zebrafish also resemble human fetal development, including modifications to the kidney (Drummond, 2005; Elizondo, Budi, & Parichy, 2010; Gerlach & Wingert, 2013) and gut (Crosnier et al, 2005; Wallace, Akhter, Smith, Lorent, & Pack, 2005); neurogenesis (Kizil, Kaslin, Kroehne, & Brand, 2012; Schmidt, Strahle, & Scholpp, 2013; Zupanc, 2011); ossification of axial and craniofacial bones (Bird & Mabee, 2003; Cubbage & Mabee, 1996; Elizondo et al, 2005; Kimmel, DeLaurier, Ullmann, Dowd, & McFadden, 2010); and continued, but differential, growth across the body (Parichy, Elizondo, Mills, Gordon, & Engeszer, 2009). Research focused on postembryonic stages has further made significant inroads toward understanding the development of the lateral line (Ghysen, Wada, & Dambly-Chaudière, 2014; Thomas, Cruz, Hailey, & Raible, 2015; Wada & Kawakami, 2015), pigment pattern (Kondo and Watanabe, 2015; Parichy & Spiewak, 2015; Singh & Nüsslein-Volhard, 2015), skeleton (Akiva et al, 2015; Eames et al, 2013), heart (Matrone, Wilson, Mullins, Tucker, & Denvir, 2015; Singleman & Holtzman, 2012), microbiome (Burns et al, 2015; Roeselers et al, 2011; Stephens et al, 2015), and lipid stores (Flynn, Trent, & Rawls, 2009; Minchin & Rawls, 2011). Investigating these and other postembryonic processes in zebrafish can lend critical insight into the conserved mechanisms by which postembryonic development occurs in humans.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that flavopiridol causes CDK9 inactivation as confirmed by Western blot analysis showing reduced phosphorylation of the Serine 2 (P-Ser2), the direct target of CDK9 27 . Chao and Price 16 found a similar result in Drosophila where they detected reduced 32 P-incorporated-RNA polymerase II following exposure to flavopiridol.…”
Section: Discussionmentioning
confidence: 64%